PENGGUNAAN BAHASA PADA ANAK USIA 4 TAHUN SEBAGAI PENGAJARAN DI LINGKUNGAN KELUARGA - Yunia Utari; Dian Nuzulia Armariena (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— This study aims to determine the use of language in children aged four years in the family environment on the road Prince Ratu Perum Atlet Type 100 Block A3 No.04 Rt.062 Rw.17 Jakabaring, Palembang. The method used in this research is descriptive method. Data analysis technique used in this research is observation. The author observes directly the child who was a study sample for nearly eight weeks. The sample data used in this research is Nayla Syaurah Nafisah. The results of the data obtained can show that there are variations of language that children use to the family environment because the father came from Central Java and Palembang mother. For example, the father asked